2003
DOI: 10.2752/089279303786992071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aquariums on electroconvulsive therapy patients

Abstract: This study investigates the effect of an aquarium on pre-treatment anxiety, fear. frustration, and depression in electroconvulsive therapy (ECT) patients. Forty-two patients consecutively referred for ECT were rotated between rooms with and without aquariums. Self report measures of depression, anxiety, fear, and frustration were obtained, along with heart rate and blood pressure measurements. Preliminary mixed-model, repeated measures analysis of variance (ANOVA) revealed no significant differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
(28 reference statements)
0
49
1
Order By: Relevance
“…The current results thus demonstrate that engaging in contact with a dog, a fish, or a plant for an intervention time of no longer than 5 minutes can result in anxiety alleviation in a non-clinical setting. It may be surprising that the three experimental groups did not statistically differ from each other, as previous studies have shown different results; for example, only a trend toward significance for contact with fish (Barker, Rasmussen and Best 2003). The fact that the methodological settings (including the experimenter), the measuring instruments, and the duration of the intervention period were all identical for the experimental and control groups may be responsible for this finding.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The current results thus demonstrate that engaging in contact with a dog, a fish, or a plant for an intervention time of no longer than 5 minutes can result in anxiety alleviation in a non-clinical setting. It may be surprising that the three experimental groups did not statistically differ from each other, as previous studies have shown different results; for example, only a trend toward significance for contact with fish (Barker, Rasmussen and Best 2003). The fact that the methodological settings (including the experimenter), the measuring instruments, and the duration of the intervention period were all identical for the experimental and control groups may be responsible for this finding.…”
Section: Discussioncontrasting
confidence: 50%
“…Using the public speech paradigm, it has been discovered that interaction with a therapy dog and its handler alleviates subjective anxiety in students before giving a public speech, whereas interaction with a friendly person does not (Morgan 2009). Although less popular in empirical studies, even fish show a trend toward reducing anxiety (Barker, Rasmussen and Best 2003). In Barker, Rasmussen and Best's (2003) study it was shown that when comparing patients attending electroconvulsive therapy in a room, either with or without a fish tank, a trend toward a lower level of anxiety was found in the group of patients who had the fish tank compared with those patients who did not.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies of the health effects of pet ownership rely on cross-sectional observational studies comparing people who own pets with people who do not (Barker, Rasmussen, & Best, 2003). Cross-sectional observational studies of the relationship between pet owner and health range from studies using convenience samples or small groups to studies involving nationally representative samples/surveys (Parslow, Jorm, Christensen, Rodgers, & Jacomb, 2005).…”
Section: Pet Ownershipmentioning
confidence: 99%
“…Bonding with animals has been found to affect the general emotional well being of people (Levinson, 1984;Mason & Hagan, 1999;Poresky, Hendrix, Mosier, & Samuelson, 1988;Risley-Curtiss, Holley, & Wolf, 2006). Animals have specifically been shown to reduce anxiety and fear prior to patients undergoing medical treatment (Barker, Pandurangi, & Best, 2003;Barker, Rasmussen, & Best, 2003) and for health care professionals (Barker, Pandurangi et al, 2003). Contact with animals has also been shown to have positive physiological effects (Hoffman, 1991;Wells, 1998) and to provide companionship for the elderly (Banks & Banks, 2005) and especially for children of single parents (Bodsworth & Coleman, 2001).…”
Section: Introductionmentioning
confidence: 95%